2022
DOI: 10.3390/ijms23126763
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Role of GA3 in Regulating the Asynchronism of Floral Bud Differentiation and Development in Heterodichogamous Cyclocarya paliurus (Batal.) Iljinskaja

Abstract: Cyclocarya paliurus is an important medical plant owing to the diverse bioactive compounds in its leaves. However, the heterodichogamy with female and male functions segregation within protandry (PA) or protogyny (PG) may greatly affect seed quality and its plantations for medicinal use. To speculate on the factor playing the dominant role in regulating heterodichogamy in C. paliurus, based on phenotypic observations, our study performed a multi comparison transcriptome analysis on female and male buds (PG and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…To investigate the potential role of CpC5-MTases and CpdMTases in heterodichogamy, based on previous research results [ 17 , 23 , 30 ], correlation analysis was performed on the differential genes in the lowering process of PA and PG. Figure 8 illustrated some genes that may play roles in heterodichogamy, such as ERFs , Trihelix-1 , and GA synthesis genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the potential role of CpC5-MTases and CpdMTases in heterodichogamy, based on previous research results [ 17 , 23 , 30 ], correlation analysis was performed on the differential genes in the lowering process of PA and PG. Figure 8 illustrated some genes that may play roles in heterodichogamy, such as ERFs , Trihelix-1 , and GA synthesis genes.…”
Section: Resultsmentioning
confidence: 99%
“…In C. paliurus , Qu et al [ 23 ] found that GA 3 positively regulated the physiological differentiation and germination of floral buds (S2), and GA-related DEGs play central roles in regulating flower development. In addition, Meijón et al [ 43 ] detected that global DNA methylation in azalea treated with a GA biosynthesis inhibitor during the floral transition could promote flowering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the function of a given gene can be inferred from its homologous genes ( Yue et al., 2016 ; Qu et al., 2022 ). Therefore, Arabidopsis orthologs were used to predict the regulatory network of these three candidate genes ( CpbHLH36/68/146 ) in this study.…”
Section: Discussionmentioning
confidence: 99%
“…18S ribosomal RNA as an internal control was carried out. The methods for calculating relative gene expression were introduced by previous study [44].…”
Section: Expression Analysis Of Selected Sabzip Genesmentioning
confidence: 99%